3-Hydroxyquinazoline derivatives, analogues of erastin, induced ferroptosis in breast cancer cells - L. M. Borisova; V. N. Osipov; I. S. Golubeva; M. P. Kiseleva; D. A. Hochenkov; A. A. Vartanyan (Успехи молекулярной онкологии)
Introduction. Early malignant tumor detection programs have significantly increased the survival rate of breast cancer patients but the results of drug therapy for this pathology are not always highly effective. Recently discovered iron-dependent cell death, ferroptosis, makes it a promising therapeutic target to reduce the recurrence rates.Objective – to study the induction of ferroptosis in breast cancer cells MCF-7 by quinazoline derivatives synthesized at the Research Institute of Experimental Diagnostics and Therapy of Tumors of the N.N. Blokhin National Medical Research Center of Oncology, Ministry of Health of Russia and to evaluate its antitumor activity on transplanted breast carcinoma Ca-755.Materials and methods. Derivatives of 3-hydroxyquinazoline were obtained by chemical synthesis and have a purity of at least 95 %. In this study 2D cultivation of MCF7 cells, phase-contrast and fluorescence microscopy, and a model of experimental growth of breast carcinoma Ca-755 in female hybrids of immunocompetent mice F1 (C57Bl/6 × DBA/2) were used.Results. Five derivatives of 3-hydroxyquinazoline, analogues of erastine, were studied in this work. The ferroptotic cell death was identified by the level of lipid peroxidation at the concentrations of 1/3 and 1/5 IC50. The level of lipid peroxidation induced by compound 3 was comparable with the activity of erastin in MCF7 cells at both 1/3 and 1/5 of IC50, the activity of the other four quinazoline derivatives was 50–70 % of the activity of erastin. In in vivo experiments at a dose of 30 mg/kg the antitumor efficacy of the compound 3 was higher than that of erastin at the same dose.Conclusion. The data obtained suggest that quinazoline derivative 3 might be considered as a promissisng antitumor agent to treat breast cancer.